Recruitment and Retention of Parents of Adolescents in a Text Messaging Trial (MyTeen): Secondary Analysis From a Randomized Controlled Trial - Joanna Ting Wai Chu; Angela Wadham; Yannan Jiang; Karolina Stasiak; Matthew Shepherd; Christopher Bullen (JMIR Publications, 2021)
BackgroundParenting programs are well established as an effective strategy for enhancing both parenting skills and the well-being of the child. However, recruitment for family programs in clinical and nonclinical settings remains low. ObjectiveThis study aims to describe the recruitment and retention methods used in a text messaging program (MyTeen) trial for parents of adolescents (10-15 years) and identify key lessons learned. We aim to provide insights and direction for researchers who seek to recruit parents and build on the limited literature on recruitment and retention strategies for parenting program trials. MethodsA recruitment plan was developed, monitored, and modified as needed throughout the course of the project. Strategies to facilitate recruitment were identified (eg, program content and recruitment material, staff characteristics, and study procedures). Traditional and web-based recruitment strategies were used. ResultsOver a 5-month period, 319 parents or caregivers expressed interest in our study, of which 221 agreed to participate in the study, exceeding our recruitment target of 214 participants. Attrition was low at the 1-month (4.5% overall; intervention group: n=5, 4.6%; control group: n=5, 4.5%) and 3-month follow-ups (9% overall; intervention group: n=10, 9.2%; control group: n=10, 8.9%). ConclusionsThe use of web-based recruitment strategies appeared to be most effective for recruiting and retaining parents in a text-messaging program trial. However, we encountered recruitment challenges (ie, underrepresentation of ethnic minority groups and fathers) similar to those reported in the literature. Therefore, efforts to engage ethnic minorities and fathers are needed. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12618000117213; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=374307